Socio-Political Figurations of Our Digital Everyday: Reflecting on Virilio’s Notions of Dromology, Civilianisation of Military Technologies, and the Information Bomb - Adi Kuntsman (Media Theory)
The essay is a meditation on Paul Virilio’s legacy and its relevance today, focusing specifically on accelerated time; civilianisation of military technologies, and the information bomb. The author discusses the complex and unevenly distributed effects of the digital era, raising a set of questions, such as: Whose time is accelerating? What happens when everyday culture is militarised, while military technologies are civilianised? How does the information bomb explode beyond the visual?  Reflecting on the prophetic character of Virilio’s theorising, the author argues that in the days of platform labour, disappearing job stability, as well as mass imprisonments and growing precarity, we need new ways of thinking about the right to time, and about the slow violence of both acceleration and timelessness. In the days of “smart” warfare, digitally-operated borders, biometric surveillance, as well as of global spectacles of “real life” killing and dying we need to fundamentally rethink the meaning of “civilianised” and “militarised”. In the days of massive celebration of AI, smart technologies and the overall digitisation, we need to envision new forms of (data) justice, to live in the aftermath of the exploded information bomb and its fire that continues burning.